Finances for small-scale industry in India - Ramakrishna, Kothapalli Tatachar (New York: Asia Pub. House, 1962)
The book is based on a study limited to financial assistance by the State in the shape of direct credit under the State Aid to industries Acts, non-financial assistance in the form of external aids and credit.
Based on the author's thesis, University of Madras.
Includes bibliography.
occ 15/01/2019
Loans
Keywords: Small business; Small scale industry; Finance - small business; India